Surface-treated metal plate
Patent Information
- Application Number
- JP2020189316
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-13
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2040-11-13
AI Technical Summary
【0012】 本発明によれば、従来のクロメート被膜と同程度の潤滑性を有する被膜を備えた表面処理金属板を提供できる。
Smart Images

Figure 0007641726000005 
Figure 0007641726000001 
Figure 0007641726000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a surface-treated metal sheet. [Background technology]
[0002] Conventionally, steel sheets having a zinc-containing plating layer have been widely subjected to anti-rust treatment using chromate, such as hexavalent chromate, and, if necessary, have been coated with an organic resin to impart higher levels of corrosion resistance, fingerprint resistance, scratch resistance, lubricity, etc., and then top-coated with various types of paint.
[0003] In recent years, there has been a trend to avoid chromate treatment due to growing environmental concerns. Since the chromate treatment layer itself has high corrosion resistance and paint adhesion, it is expected that these performances will be significantly reduced if the chromate treatment is not performed. Therefore, there has been a demand to form a rust-preventive layer with good corrosion resistance and paint adhesion by only one-step treatment with organic resin, without performing the base treatment by chromate treatment.
[0004] Patent Document 1 describes a surface metal treatment material having a composite coating containing each of the components obtained by applying a surface treatment metal agent consisting of an organosilicon compound, at least one fluoro compound selected from titanium hydrofluoric acid or zirconium hydrofluoric acid, phosphoric acid, and a vanadium compound to the surface of a metal material and then drying it.
[0005] Patent Document 2 describes a surface metal treatment material provided on a metal surface with a composite coating containing an organosilicon compound, at least one fluoro compound selected from titanium hydrofluoric acid or zirconium hydrofluoric acid, phosphoric acid, a vanadium compound, and at least one lubricant selected from the group consisting of aqueous dispersion-type polyethylene wax, polypropylene wax, and polytetrafluoroethylene, which has a number average particle size of 0.01 μm to 1.0 μm and a softening temperature of 100° C. or higher.
[0006] Patent Document 3 describes a chromate-free surface-treated metal material having a coating formed by applying an aqueous treatment agent containing an organosilicon compound and an organofluorine compound having a perfluoroalkyl group to the surface of the metal material and drying or baking the aqueous treatment agent.
[0007] Patent Document 4 describes a coating composition containing an organosilicon compound as a film-forming component, and containing at least one metal compound selected from the group consisting of titanium compounds and zirconium compounds, a phosphoric acid compound, and a fluorine compound as inhibitor components, and the ratio of cyclic siloxane bonds to linear siloxane bonds in the organosilicon compound is 1090 to 1100 cm, which indicates cyclic siloxane bonds by FT-IR reflection method. -1 The absorbance W1 and linear siloxane bond at 1030-1040 cm -1 The document describes a surface-treated metal material having a composite coating on the surface of the metal material, the composite coating having a ratio W1 / W2 of the absorbance of W1 to the absorbance W2 of 1.0 to 2.0. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Patent No. 4776458 [Patent Document 2] Patent No. 5335434 [Patent Document 3] Patent No. 4709942 [Patent Document 4] Patent No. 5336002 Summary of the Invention [Problem to be solved by the invention]
[0009] Incidentally, the lubricity of plated steel sheets on which a coating is formed by chemical conversion treatment is determined by the coating on the outermost surface. Lubricity is evaluated by the dynamic friction coefficient of the coating surface, etc. When replacing a conventional chromate coating with a chromate-free coating, the chromate-free coating is required to have the same degree of lubricity as the chromate coating. If the lubricity of the chromate-free coating is reduced, stacking of multiple plated steel sheets is likely to occur when stacked flat, which was not a problem with chromate coatings. In addition, if the lubricity of the chromate-free coating differs from that of the chromate coating, for example, when performing roll forming on plated steel sheets, it is necessary to readjust the processing setting conditions. However, no attempt has been made to bring the lubricity of the chromate-free coating closer to that of the chromate coating.
[0010] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a surface-treated metal sheet provided with a coating having the same degree of lubricity as conventional chromate coatings. [Means for solving the problem]
[0011] The means for solving the above problems are as follows. [1] A steel plate; a zinc-containing plating layer formed on the steel sheet; formed on the plating layer Chromate-free and a coating, The coating contains an organosilicon compound, a phosphoric acid compound, and a fluorine compound, A surface-treated metal sheet characterized in that the surface roughness of a rectangular region on the surface of the coating, with each side of the region being 5 μm, satisfies the following: arithmetic mean height Sa, maximum height Sz, and root mean square roughness Sq, respectively: arithmetic mean height Sa is 0.10 to 10 nm, maximum height Sz is 1.0 to 1000 nm, and root mean square roughness Sq is 0.10 to 100 nm. [2] When the surface roughness of a rectangular area of the surface of the coating having sides of 1 μm is expressed in terms of the arithmetic mean height Sa, the maximum height Sz, and the root mean square roughness Sq, the arithmetic mean height Sa is 0.10 to 10 nm, the maximum height Sz is 1.0 to 1000 nm, and the root mean square roughness Sq is 0.10 to 100 nm. death, The coefficient of dynamic friction is in the range of 0.2 to 0.5. The surface-treated metal sheet according to [1], [3] A surface-treated metal sheet according to [1] or [2], characterized in that the coating contains, within a rectangular region of 1 μm on a side, 1 to 100 granular organosilicon compounds each having a long diameter of 10 nm or more and 300 nm or less. [4] The average chemical composition of the plating layer is, in mass%, Al: over 4.0% to less than 25.0% Mg: over 1.0% to less than 12.5% Sn: 0%~20%, Bi: 0% to less than 5.0% In: 0% to less than 2.0% Ca: 0%~3.0%, Y: 0%~0.5%, La: 0% to less than 0.5%, Ce: 0% to less than 0.5%, Si: 0% to less than 2.5% Cr: 0% to less than 0.25%, Ti: 0% to less than 0.25% Ni: 0% to less than 0.25% Co: 0% to less than 0.25% V: 0% to less than 0.25%, Nb: 0% to less than 0.25% Cu: 0% to less than 0.25% Mn: 0% to less than 0.25% Fe: 0%~5.0%, Sr: 0% to less than 0.5%, Sb: 0% to less than 0.5% Pb: 0% to less than 0.5% B: Contains less than 0% to 0.5% The surface-treated metal sheet according to any one of [1] to [3], wherein the remainder is Zn and impurities. Effect of the Invention
[0012] According to the present invention, it is possible to provide a surface-treated metal sheet having a coating film having the same degree of lubricity as a conventional chromate coating film. [Brief description of the drawings]
[0013] [Figure 1] 1 is a schematic cross-sectional view of a surface-treated metal sheet according to an embodiment of the present invention. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] In order to realize a coating that has the same level of lubricity as conventional chromate coatings, and also has paint adhesion and corrosion resistance, we came up with a coating design that controls the roughness in the microscopic area of the coating surface. Generally, roughness is measured in the millimeter or centimeter range using a roughness meter, but we believe that it is the roughness in the micrometer range that actually governs lubricity (dynamic friction coefficient) and paint adhesion, and so we designed the following chromate-free coating.
[0015] In other words, in order to improve paint adhesion and control lubricity (dynamic friction coefficient) through physical actions, it was discovered that when the surface roughness in a rectangular area with one side measuring 5 μm is expressed as the arithmetic mean height Sa, the maximum height Sz, and the root mean square roughness Sq, respectively, an arithmetic mean height Sa of 0.10 to 10 nm, a maximum height Sz of 1.0 to 1000 nm, and a root mean square roughness Sq of 0.10 to 100 nm can be achieved to achieve lubricity (dynamic friction coefficient) equivalent to that of a chromate coating.
[0016] In addition, it was found that in a rectangular region with sides each measuring 1 μm, the lubricity can be more appropriately controlled by satisfying the following conditions: arithmetic mean height Sa is 0.10 to 10 nm, maximum height Sz is 1.0 to 1000 nm, and root mean square roughness Sq is 0.10 to 100 nm.
[0017] Furthermore, in order to improve paint adhesion through chemical action, it was found that by making the main component of the coating an organosilicon compound, the lubricity (dynamic friction coefficient) becomes equivalent to that of chromate and paint adhesion is also improved.
[0018] Furthermore, they have found that it is effective to add a phosphate compound and a fluorine compound to the coating as components for improving corrosion resistance without affecting lubricity and coating adhesion.
[0019] To realize the above design concept, it was found that the roughness of micro-areas on the coating surface can be controlled within the above range by applying a surface treatment metal agent with a viscosity of 0.5 mPa·s to 2.0 mPa·s, allowing it to dry naturally for 0.2 to 10 seconds in an atmosphere of 10 to 35°C and a relative humidity of 30 to 90% immediately after application, and then further drying by heating.
[0020] Hereinafter, a surface-treated metal sheet according to an embodiment of the present invention will be described. The surface-treated metal sheet of this embodiment has a steel sheet, a zinc-containing plating layer formed on the steel sheet, and a coating formed on the plating layer, the coating containing an organosilicon compound, a phosphate compound, and a fluorine compound, and when the surface roughness of a rectangular area with sides of 5 μm on the surface of the coating is expressed respectively as the arithmetic mean height Sa, the maximum height Sz, and the root mean square roughness Sq, the surface-treated metal sheet satisfies the arithmetic mean height Sa of 0.10 to 10 nm, the maximum height Sz of 1.0 to 1000 nm, and the root mean square roughness Sq of 0.10 to 100 nm. Furthermore, when the surface roughness in a rectangular region with sides of 1 μm on the coating surface is expressed in terms of the arithmetic mean height Sa, the maximum height Sz, and the root mean square roughness Sq, it is preferable that the arithmetic mean height Sa be 0.10 to 10 nm, the maximum height Sz be 1.0 to 1000 nm, and the root mean square roughness Sq be 0.10 to 100 nm. It is also preferable that the coating surface contains 1 to 100 granular organosilicon compounds each having a major axis of 10 nm to 300 nm within a rectangular region having sides of 1 μm.
[0021] In the following description, the "%" for the content of each element in the chemical composition means "mass %." Furthermore, a numerical range expressed using "~" means a range that includes the numerical values before and after "~" as the lower and upper limits. When the numerical values before and after "~" are followed by "more than" or "less than," the numerical range does not include these numerical values as the lower or upper limit.
[0022] <Steel plate 11> As shown in FIG. 1, the surface-treated metal sheet 1 according to this embodiment has the same lubricity as that obtained when a chromate coating is formed, due to the plating layer 12 and the composite coating 13. Moreover, the surface-treated metal sheet 1 according to this embodiment also has excellent corrosion resistance and paint adhesion of the coating. Therefore, the steel sheet 11 is not particularly limited. It may be determined according to the product to which it is applied and the required strength and sheet thickness. The material of the steel sheet 11 may be various steel sheets such as general steel, Ni pre-plated steel, Al killed steel, ultra-low carbon steel, high carbon steel, various high tensile steels, and some high alloy steels (steels containing strengthening elements such as Ni and Cr). Moreover, the steel sheet 11 is not particularly limited in terms of the conditions of the steel sheet manufacturing method (hot rolling method, pickling method, cold rolling method, etc.). Furthermore, the steel sheet 11 may be a steel sheet on which a metal film or alloy film of less than 1 μm, such as Zn, Ni, Sn, or alloys thereof, is formed. Examples of the steel sheet 11 include a hot-rolled steel sheet as described in JIS G3193:2008 and a cold-rolled steel sheet as described in JIS G3141:2017.
[0023] <Plating layer 12> The plating layer 12 provided on the surface-treated metal sheet 1 according to this embodiment is formed on the surface of the steel sheet 11 and contains zinc. The zinc content may be, for example, 50% by mass or more. The plating layer 12 may also contain aluminum. Furthermore, it may further contain magnesium. The corrosion resistance of the plating layer 12 improves in the order of a plating layer containing zinc, a plating layer containing zinc and aluminum, and a plating layer containing zinc, aluminum, and magnesium. In this embodiment, any of these plating layers may be provided. When aluminum is contained, it may be less than 25.0% by mass, and when magnesium is contained, it may be less than 12.5% by mass.
[0024] Examples of the zinc-containing plating layer 12 include a hot-dip galvanized layer or an electrolytic galvanized layer made of zinc and the remaining impurities. Examples of the zinc and aluminum-containing plating layer 12 include a hot-dip galvanized layer made of zinc, aluminum, and the remaining impurities, and a hot-dip galvanized layer further containing an additive element. Examples of the zinc, aluminum, and magnesium-containing plating layer 12 include a hot-dip galvanized layer made of zinc, aluminum, magnesium, and the remaining impurities, and a hot-dip galvanized layer further containing an additive element.
[0025] The chemical composition of the plating layer 12, which contains zinc, aluminum, and magnesium, will be described below. The plating layer 12 preferably has a chemical composition of Al: more than 4.0% and less than 25.0%, Mg: more than 1.0% and less than 12.5%, Sn: 0% to 20%, Bi: 0% to less than 5.0%, In: 0% to less than 2.0%, Ca: 0% to 3.0%, Y: 0% to 0.5%, La: 0% to less than 0.5%, Ce: 0% to less than 0.5%, Si: 0% to less than 2.5%, Cr: 0% to less than 0.25%, Ti: 0% to less than 0.25%, Ni: 0% to less than 0.25%, Co: 0% to less than 0.25%, V: 0% to less than 0.25%, Nb: 0% to less than 0.25%, Cu: 0% to less than 0.25%, Mn: 0% to less than 0.25%, Fe: 0% to 5.0%, Sr: 0% to less than 0.5%, Sb: 0% to less than 0.5%, Pb: 0% to less than 0.5%, B: 0% to less than 0.5%, and the balance being Zn and impurities.
[0026] [Al: over 4.0% to less than 25.0%] Al is an element effective for ensuring corrosion resistance in the plating layer 12 containing aluminum (Al), zinc (Zn), and magnesium (Mg). To fully obtain the above effects, it is preferable for the Al content to exceed 4.0%. On the other hand, if the Al content is 25.0% or more, the corrosion resistance of the cut end surface of the plating layer 12 decreases. Therefore, the Al content is preferably less than 25.0%.
[0027] [Mg: over 1.0% to less than 12.5%] Mg is an element that has the effect of increasing the corrosion resistance of the plating layer 12. In order to sufficiently obtain this effect, it is preferable that the Mg content be more than 1.0%. On the other hand, if the Mg content is 12.5% or more, the effect of improving corrosion resistance is saturated and the workability of the coating layer 12 is reduced. In addition, problems in manufacturing occur, such as an increase in the amount of dross generated in the coating bath. Therefore, it is preferable that the Mg content is less than 12.5%.
[0028] The plating layer 12 may contain Al and Mg, with the balance being Zn and impurities, but may further contain the following elements as necessary.
[0029] [Sn:0%~20%] [Bi: 0% to less than 5.0%] [In: 0% to less than 2.0%] When these elements are contained in the plating layer 12, Mg is formed as a new intermetallic compound phase in the plating layer 12. 2 Sn phase, Mg 3 Bi 2 Phase, Mg 3 In equivalent is formed. These elements form an intermetallic compound phase only with Mg, without forming an intermetallic compound phase with either Zn or Al, which mainly constitute the plating layer 12. When a new intermetallic compound phase is formed, the weldability of the plating layer 12 changes significantly. Since all intermetallic compound phases have high melting points, they do not evaporate even after welding and remain as intermetallic compound phases. Mg, which is originally prone to oxidization by welding heat to form MgO, does not oxidize by forming an intermetallic compound phase with Sn, Bi, or In, and is likely to remain as an intermetallic compound phase as the plating layer 12 even after welding. Therefore, the presence of these elements improves corrosion resistance and sacrificial corrosion resistance, and improves corrosion resistance around the welded part. To obtain the above effects, it is preferable to set the content of each to 0.05% or more. Of these, Sn is preferred because it is a low melting point metal and can be easily incorporated into the plating bath without impairing the properties of the plating bath. The upper limits of these elements are set to 20% or less for Sn, less than 5.0% for Bi, and less than 2.0% for In.
[0030] [Ca: 0%~3.0%] When Ca is contained in the coating layer 12, the amount of dross that is likely to be formed during coating operation decreases with an increase in the Mg content, improving coating manufacturability. Therefore, Ca may be contained. To obtain this effect, the Ca content is preferably 0.1% or more. On the other hand, if the Ca content is high, the corrosion resistance of the flat parts of the plating layer 12 itself tends to deteriorate, and the corrosion resistance around the welded parts may also deteriorate. Therefore, even if Ca is contained, the Ca content is preferably 3.0% or less.
[0031] [Y:0%~0.5%] [La: 0% to less than 0.5%] [Ce: 0% to less than 0.5%] Y, La, and Ce are elements that contribute to improving corrosion resistance. To obtain this effect, it is preferable to contain at least one of them in an amount of 0.05% or more. On the other hand, if the contents of these elements are excessive, the viscosity of the plating bath increases, and the preparation of the plating bath itself often becomes difficult, making it impossible to produce a surface-treated metal sheet 11 with good plating properties. Therefore, even if these elements are contained, it is preferable that the Y content be 0.5% or less, the La content be less than 0.5%, and the Ce content be less than 0.5%.
[0032] [Si: 0% to less than 2.5%] Si is an element that forms a compound together with Mg and contributes to improving corrosion resistance. In addition, Si is also an element that has the effect of suppressing the formation of an excessively thick alloy layer between the surface of the steel sheet 11 and the plating layer 12 when the plating layer 12 is formed on the steel sheet 11, thereby enhancing the adhesion between the steel sheet 11 and the plating layer 12. To obtain this effect, the Si content is preferably 0.1% or more, and more preferably 0.2% or more. On the other hand, if the Si content is 2.5% or more, excessive Si precipitates in the plating layer 12, which not only reduces the corrosion resistance but also reduces the workability of the plating layer 12. Therefore, the Si content is preferably less than 2.5%, and more preferably 1.5% or less.
[0033] [Cr: 0% to less than 0.25%] [Ti: 0% to less than 0.25%] [Ni: 0% to less than 0.25%] [Co: 0% to less than 0.25%] [V: 0% to less than 0.25%] [Nb: 0% to less than 0.25%] [Cu: 0% to less than 0.25%] [Mn: 0% to less than 0.25%] These elements contribute to improving corrosion resistance. In order to obtain this effect, the content of each element is preferably 0.05% or more. On the other hand, if the contents of these elements are excessive, the viscosity of the plating bath increases, making it difficult to prepare the plating bath itself in many cases, and it is not possible to produce a surface-treated metal sheet 1 with good plating properties. Therefore, it is preferable that the contents of each element are each less than 0.25%.
[0034] [Fe:0%~5.0%] When the plating layer 12 is manufactured, Fe is mixed into the plating layer 12 as an impurity. It may be contained up to about 5.0%, but within this range, the adverse effect on the effect of the surface metal-treated sheet 11 according to this embodiment is small. Therefore, the Fe content is preferably 5.0% or less.
[0035] [Sr: 0% to less than 0.5%] [Sb: 0% to less than 0.5%] [Pb: 0% to less than 0.5%] When Sr, Sb, and Pb are contained in the plating layer 12, the appearance of the plating layer 12 changes, spangles are formed, and an improvement in metallic luster is confirmed. To obtain this effect, it is preferable that the content of each of Sr, Sb, and Pb is 0.05% or more. On the other hand, if the contents of these elements are excessive, the viscosity of the plating bath increases, making it difficult to prepare the plating bath itself in many cases, and it is not possible to produce a surface-treated metal sheet 1 with good plating properties. Therefore, it is preferable that the Sr content is less than 0.5%, the Sb content is less than 0.5%, and the Pb content is less than 0.5%.
[0036] [B: 0% to less than 0.5%] When B is contained in the plating layer 12, it combines with Zn, Al, and Mg to form various intermetallic compound phases. These intermetallic compounds have the effect of improving LME (liquid metal embrittlement). To obtain this effect, the B content is preferably 0.05% or more. On the other hand, if the B content is excessive, the melting point of the plating bath increases significantly, the plating operability deteriorates, and a surface-treated metal sheet 1 with good plating properties cannot be obtained. Therefore, the B content is preferably less than 0.5%.
[0037] The coating weight of the plating layer 12 is not limited, but is set to 10 g / m 2 On the other hand, the coating weight is preferably 200 g / m or more. 2 If it exceeds 200g / m, the corrosion resistance will saturate and it will be economically disadvantageous. 2 It is preferable that:
[0038] <Coating 13> The coating 13 provided on the surface of the plating layer 12 of the surface-treated metal sheet 1 according to this embodiment contains an organosilicon compound, a phosphate compound, and a fluorine compound. The coating 13 may further contain a zirconium compound or a vanadium compound. The coating 13 according to this embodiment does not contain a Cr compound and is a so-called chromate-free coating. The coating 13 contains an organosilicon compound, a phosphate compound, and a fluorine compound, so that the surface-treated metal sheet 1 can be provided with corrosion resistance and paint adhesion.
[0039] In this embodiment, the organosilicon compound contained in the coating 13 is not limited, but may be obtained, for example, by blending a silane coupling agent (A) containing one amino group in the molecule with a silane coupling agent (B) containing one glycidyl group in the molecule in a solids mass ratio [(A) / (B)] of 0.5 to 2.0, preferably 0.5 to 1.7. The blending ratio of the silane coupling agent (A) to the silane coupling agent (B) is preferably 0.5 to 2.0, preferably 0.5 to 1.7, in terms of the solid content mass ratio [(A) / (B)]. If the solid content mass ratio [(A) / (B)] is less than 0.5, fingerprint resistance, bath stability, and black residue resistance may be significantly reduced. Conversely, if it exceeds 2.0, water resistance may be significantly reduced, which is not preferable. [(A) / (B)] is more preferably 0.7 to 1.7, and even more preferably 0.9 to 1.1.
[0040] Examples of the silane coupling agent (A) containing one amino group include, but are not limited to, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, etc., and examples of the silane coupling agent (B) containing one glycidyl group in the molecule include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, etc.
[0041] In this embodiment, the phosphate compound contained in the coating 13 is not particularly limited, but examples thereof include phosphoric acid, ammonium phosphate, potassium phosphate, and sodium phosphate. Among these, phosphoric acid is more preferable. When phosphoric acid is used, better corrosion resistance can be obtained.
[0042] The content of the phosphoric acid compound in the coating 13 is preferably such that the average value of P / Si, which is the ratio of the solid mass of P derived from the phosphoric acid compound to the solid mass of Si derived from the organosilicon compound, is 0.15 to 0.25, since this maintains the homogeneity of the coating 13. By making the average value of P / Si 0.15 or more, there is no risk of a decrease in corrosion resistance due to a cause believed to be a lack of P. Furthermore, by making the average value of P / Si 0.25 or less, it is possible to prevent the coating 13 from becoming water-soluble.
[0043] In this embodiment, the fluorine compound contained in the coating 13 is not particularly limited, but examples thereof include hydrofluoric acid, hydroborofluoric acid, hydrofluorosilicic acid, and fluorides such as water-soluble salts thereof, and complex fluoride salts thereof. Among these, hydrofluoric acid is more preferable. When hydrofluoric acid is used, better corrosion resistance and paintability can be obtained.
[0044] In coating 13, it is preferable that the average value of F / Si, which is the ratio of the solid mass of F derived from the fluorine compound to the solid mass of Si derived from the organosilicon compound, is 0.01 to 0.15, because this ensures appropriate corrosion resistance while maintaining the homogeneity of coating 13.
[0045] The coating 13 may contain a zirconium compound. Examples of the zirconium compound include, but are not limited to, zirconium hydrofluoric acid, ammonium hexafluorozirconate, zirconium sulfate, zirconium oxychloride, zirconium nitrate, and zirconium acetate. Among these, zirconium hydrofluoric acid is more preferable. When zirconium hydrofluoric acid is used, better corrosion resistance and paintability can be obtained. In addition, zirconium hydrofluoric acid is preferable because it also acts as a fluorine compound.
[0046] Furthermore, the coating 13 may contain a vanadium compound. The vanadium compound (V) is not particularly limited, but may be vanadium pentoxide V 2 O 5 , Metavanadate HVO 3 , Ammonium metavanadate, Sodium metavanadate, Vanadium oxytrichloride VOCl 3 , vanadium trioxide V 2 O 3 , vanadium dioxide VO 2 , Vanadium oxysulfate VOSO 4 , vanadium oxyacetylacetonate VO(OC(=CH 2 )CH 2 COCH 3 ) 2 , vanadium acetylacetonate V(OC(=CH 2 )CH 2 COCH 3 ) 3 , vanadium trichloride VCl 3 Examples of vanadium compounds that can be used include vanadium compounds having a valence of 4 to 2, and the like. Vanadium compounds having a valence of 4 to 2 can also be used.
[0047] In the coating 13, it is preferable that the average value of Zr / Si, which is the ratio of the solid mass of Zr derived from the zirconium compound to the solid mass of Si derived from the organosilicon compound, is 0.06 to 0.15, since this maintains the homogeneity of the coating 13. If the average value of Zr / Si is 0.06 or more, the barrier properties are sufficient and there is no risk of a decrease in corrosion resistance. In addition, it is preferable that the average value of Zr / Si is 0.15 or less, since this ensures sufficient corrosion resistance.
[0048] In addition, in the coating 13, it is preferable that the average value of V / Si, which is the ratio of the solid mass of V derived from the vanadium compound to the solid mass of Si derived from the organosilicon compound, is 0.01 to 0.20, since the V compound is moderately precipitated in the region with low corrosion resistance while maintaining the homogeneity of the coating 13. If the average value of V / Si is 0.01 or more, the amount of V as a corrosion inhibitor becomes sufficient and there is no risk of a decrease in corrosion resistance. Furthermore, if the average value of V / Si is 0.20 or less, there is no risk of the coating becoming water-soluble.
[0049] F / Si, P / Si, Zr / Si, and V / Si can be measured using micro-X-ray fluorescence. Specifically, F / Si, P / Si, Zr / Si, and V / Si are calculated from the mass percentages of F, P, Zr, V, and Si among the detectable elements constituting the coating 13, plating layer 12, and steel sheet 11, measured using a micro fluorescent X-ray (Orbis energy dispersive micro fluorescent X-ray analyzer manufactured by AMETECH, tube voltage: 5 kV, tube current: 1 mA) with an X-ray source of Rh and a spot size of φ30 μm over an area of approximately 2.3 mm horizontally and approximately 1.5 mm vertically on the surface of the composite coating with 256 × 200 pixels.
[0050] The amount of coating 13 applied per side is 0.05 to 2.0 g / m 2 It is preferable that the thickness is 0.2 to 1.0 g / m 2 More preferably, the thickness is 0.3 to 0.6 g / m 2 It is most preferable that the coating weight is 0.05 g / m 2If the coating weight is less than 2.0 g / m, the surface of the plating layer 12 cannot be covered, and the corrosion resistance is significantly reduced, which is not preferable. 2 Above this level, the effect of improving corrosion resistance becomes saturated, so the upper limit is set at 2.0 g / m 2 The following would suffice.
[0051] Next, the surface roughness of the coating 13 of this embodiment will be described. In the coating 13 of this embodiment, when the surface roughness in a rectangular region with sides of 5 μm on its surface is expressed as the arithmetic mean height Sa, the maximum height Sz, and the root mean square roughness Sq, respectively, the arithmetic mean height Sa satisfies 0.10 to 10 nm, the maximum height Sz satisfies 1.0 to 1000 nm, and the root mean square roughness Sq satisfies 0.10 to 100 nm. Furthermore, in the coating 13 of this embodiment, when the surface roughness in a rectangular region with sides of 1 μm on its surface is expressed as the arithmetic mean height Sa, the maximum height Sz, and the root mean square roughness Sq, it is preferable that the arithmetic mean height Sa satisfies 0.10 to 10 nm, the maximum height Sz satisfies 1.0 to 1000 nm, and the root mean square roughness Sq satisfies 0.10 to 100 nm. The reasons for limiting the surface roughness will now be described.
[0052] <Surface roughness in a rectangular area with sides of 5 μm> The inventors have found that, in order to bring the lubricity of the coating 13 of this embodiment closer to that of a chromate coating, it is necessary to evaluate the surface roughness of the coating itself in a state where the influence of the surface roughness of the plating layer 12 is removed. Because the coating 13 is formed on the plating layer 12, the surface roughness of the coating 13 is influenced by the surface roughness of the plating layer 12. As a result of their investigation, the inventors have found that by setting the measurement area to a rectangular area with one side of 5 μm, the influence of the surface roughness of the plating layer 12 is reduced, making it possible to evaluate the surface roughness of the coating itself. Therefore, the measurement area for the surface roughness is set to a rectangular area with one side of 5 μm.
[0053] <Arithmetic mean height Sa: 0.10 to 10 nm> <Maximum height Sz: 1.0~1000nm> <Root mean square roughness Sq: 0.10~100nm> In this embodiment, the parameters for evaluating the surface roughness of a rectangular region of the coating 13 with sides of 5 μm are the arithmetic mean height Sa, the maximum height Sz, and the root mean square roughness Sq, which must each be within a predetermined range. In order to bring the lubricity of the coating 13 closer to that of a chromate coating, the arithmetic mean height Sa is set within a range of 0.10 to 10 nm, the maximum height Sz is set within a range of 1.0 to 1000 nm, and the root mean square roughness Sq is set within a range of 0.10 to 100 nm. If any of Sa, Sz, and Sq is outside the predetermined range, the lubricity of the coating 13 will be different from that of the chromate coating, which is not preferable.
[0054] <Surface roughness in a rectangular area with one side measuring 1 μm> The coating 13 has a surface roughness corresponding to the surface roughness of the plating layer 12. The surface roughness of the plating layer 12 is relatively large, and the surface roughness of the coating 13 reflecting the surface roughness of the plating layer 12 is a roughness of several μm to several tens of μm when measured in units of millimeters to centimeters as a measurement length. Therefore, when the coating 13 is in contact with another object, the contact area between the coating 13 and the object is microscopically seen as a collection of many point contact areas. For this reason, the present inventors have found that it is preferable to evaluate the surface roughness in an area corresponding to the point contact area in order to evaluate the lubricity of the surface of the coating 13. The present inventors have found that the lubricity of the coating 13 can be more appropriately evaluated by adding a rectangular area with a side of 1 μm to the measurement area in addition to the rectangular area with a side of 5 μm. Therefore, it is preferable to specify the surface roughness in the rectangular area with a side of 1 μm.
[0055] <Arithmetic mean height Sa: 0.10 to 10 nm> <Maximum height Sz: 1.0~1000nm> <Root mean square roughness Sq: 0.10~100nm> In this embodiment, the parameters for evaluating the surface roughness of a rectangular region of the coating 13 with sides of 1 μm are the arithmetic mean height Sa, the maximum height Sz, and the root mean square roughness Sq, which must each be within a predetermined range, as in the case of a region of 5 μm square. In order to bring the lubricity of the coating 13 closer to that of a chromate coating, the arithmetic mean height Sa is set within a range of 0.10 to 10 nm, the maximum height Sz is set within a range of 1.0 to 1000 nm, and the root mean square roughness Sq is set within a range of 0.10 to 100 nm. If any of Sa, Sz, and Sq is outside the predetermined range, the lubricity of the coating 13 will be different from that of the chromate coating, which is not preferable.
[0056] Next, the form of the organosilicon compound in the coating 13 will be described. In the coating 13 of this embodiment, it is preferable that a rectangular region on the surface with one side measuring 1 μm contains 1 to 100 granular organosilicon compounds with a long axis of 10 nm to 300 nm. This increases the lubricity when oil is applied to the surface of the coating 13, making processing easier. This is presumably because the granular organosilicon compounds form ridges on the surface of the coating 13, and the voids formed between the ridges as the ridges are formed form regions that effectively hold lubricating oil.
[0057] <Evaluation method> The evaluation method will be described below. The method for measuring Sa, Sz, and Sq in a rectangular region with sides of 5 μm is as follows. 20 regions are set as measurement regions of 5 μm square on the surface of the coating 13. The set locations are arbitrary. Then, Sa, Sz, and Sq are measured in each measurement region. The measurement device used is a scanning probe microscope (AFM5500M manufactured by Hitachi High-Tech Science Corporation), and the measurement mode is dynamic focus microscope mode. The probe used is an SI-DF20, with a tip radius of 10 nm. The average values of the measurement results for each of the 20 measurement regions are taken as Sa, Sz, and Sq in the rectangular region with sides of 5 μm on the coating surface.
[0058] Next, the method of measuring Sa, Sz, and Sq in a rectangular region with one side of 1 μm is as follows. 40 regions are set as measurement regions of 1 μm square on the surface of the coating 13. Of the 40 measurement regions, 20 measurement regions are set within the aforementioned 20 rectangular measurement regions of 5 μm, and the remaining 20 are arbitrarily set from positions different from the 5 μm rectangular region. Then, Sa, Sz, and Sq are measured in each measurement region. The measurement device, measurement mode, probe, and tip radius are as described above. Then, the average values of the measurement results of each of the 40 measurement regions are taken as Sa, Sz, and Sq in the rectangular region of 1 μm on a side of the coating surface.
[0059] Next, the number density of the organosilicon compound will be described. The measurement area set in the measurement method for Sa, Sz, and Sq in a rectangular area with one side of 1 μm is used to measure the number density of the organosilicon compound. In these multiple measurement areas, images are measured using the measurement mode of a dynamic focus microscope. The organosilicon compound in the image is identified, and the number and size of the identified organosilicon compound are measured. The average value is calculated from the measurement results in the multiple measurement areas, and this is the maximum diameter and number density.
[0060] An electron probe microanalyzer (EPMA) and a Fourier transform type micro infrared spectrophotometer (micro FT-IR) are used as means for identifying organosilicon compounds in images taken with a dynamic focus microscope. The measurement with the micro FT-IR is performed in reflection measurement mode. Si is detected using the EPMA, and the periphery of the detected Si is measured with the micro FT-IR. When an infrared spectrum corresponding to the organic part of the organosilicon compound is obtained, the region where the infrared absorption spectrum is obtained is identified as an organosilicon compound. The average values are calculated from the results of multiple measurement regions, and these are taken as the maximum diameter and number density.
[0061] The surface-treated metal sheet of this embodiment has lubricity equivalent to that of a conventional chromate coating. The surface-treated metal sheet of this embodiment can improve corrosion resistance and paint adhesion. The lubricity can be evaluated by the dynamic friction coefficient, and the coating 13 of this embodiment has a dynamic friction coefficient of 0.2 to 0.5, which is equivalent to that of a chromate coating. Regarding corrosion resistance, in a corrosion resistance evaluation using a salt spray test, the white rust occurrence rate is less than 5% after 72 hours, indicating excellent corrosion resistance. Furthermore, the secondary paint adhesion (cross-cut peel test after immersion in boiling water for 30 minutes after white paint application, Erichsen processed part peel test) achieves 80 / 100 or more.
[0062] <Method of forming the coating> Next, a preferred manufacturing method for the surface-treated metal sheet 1 according to this embodiment will be described. The surface-treated metal sheet according to this embodiment can be obtained by a manufacturing method including a plating step of immersing a steel sheet 11 in a plating bath containing Zn, Al, and Mg to form a plating layer 12 on the surface of the steel sheet 11, a coating step of coating the plating layer 12 with a surface-treatment metal agent, and a coating formation step of heating (baking) the steel sheet 11 coated with the surface-treatment metal agent to form a coating containing an organosilicon compound, a phosphate compound, and a fluorine compound.
[0063] [Plating process] The plating process is not particularly limited, and may be carried out in a conventional manner so as to obtain sufficient plating adhesion. Furthermore, there is no limitation on the method of manufacturing the steel sheet 11 to be subjected to the plating step.
[0064] [Coating process] In the coating step, a surface treatment metal agent containing an organosilicon compound, a phosphate compound, and a fluorine compound is coated on the plating layer 12 of the steel sheet 11 . It is preferable to adjust the ratio of the phosphoric acid compound and the fluorine compound to the organosilicon compound in accordance with the ratio of the target coating film. The pH of the surface treatment metal agent can be adjusted using a pH adjuster such as organic acids such as acetic acid and lactic acid, inorganic acids such as hydrofluoric acid, ammonium salts, or amines.
[0065] The application method is not limited. For example, application can be performed using a roll coater, a bar coater, a spray, etc. When application is performed using a roll coater, the film thickness can be easily controlled by adjusting the peripheral speed ratio, and excellent productivity can be obtained.
[0066] In this embodiment, after the surface treatment metal agent is applied onto the plating layer 12 to form a coating film, the temperature is maintained at 10 to 35°C and a humidity of 30 to 90% for 0.2 to 10 seconds until drying begins. It is believed that by maintaining the temperature for 0.2 seconds or more, more preferably 0.5 seconds or more, after application until drying, the moisture in the outermost layer of the coating film evaporates, forming the surface state of the coating film 13 according to this embodiment. The preferred humidity range is 50 to 80%.
[0067] If the humidity is less than 30%, the drying will proceed too quickly, and if the humidity is more than 90%, the drying will not proceed sufficiently, making it impossible to form the coating 13 according to this embodiment. If the holding time is less than 0.2 seconds, the drying will not proceed sufficiently, making it impossible to form the coating 13 according to this embodiment. Note that even if the time from the formation of the coating film to the start of drying exceeds 10 seconds, the effect will not improve and productivity will decrease, so the holding time is set to 10 seconds or less. The time for holding the coating film in this state is preferably 10 seconds or less, and more preferably 5 seconds or less.
[0068] The start of the holding time for natural drying is immediately after application of the surface treatment metal agent, and the end of the holding time is the start of heating for heat drying.
[0069] Next, the coating film that has been held for a predetermined time is heated and dried. The temperature at which the coating film is dried is selected so that the volatile components in the surface-treating metal agent volatilize. Specifically, it is preferable that the maximum plate temperature (PMT) at which the coating film is dried is within the range of 60 to 150°C. Examples of the drying method for drying the coating film include hot air drying and oven drying.
[0070] In this manner, the surface-treated metal sheet of the present embodiment can be manufactured. EXAMPLES
[0071] The steel sheets were immersed in a plating bath to obtain metal sheets M-1 to M-7 having the plating layers shown in Table 1. In Table 1, for example, "Zn-19%Al-6%Mg-1.5%Sn-0.5%Ca-0.2%Si" means, by mass%, 19% Al, 6% Mg, 1.5% Sn, 0.5% Ca, and 0.2% Si, with the balance being Zn and impurities. The coating weight of the plating layer was 90 g / m 2 It was decided.
[0072] The steel sheet used was a cold-rolled steel sheet described in JIS G3141:2017.
[0073] After degreasing the steel sheet surface, the steel sheets having plating layers M-1 to M-7 were coated with a roll coater using a coating liquid of a surface treatment metal agent containing an organosilicon compound, a fluorine compound, a phosphate compound, and a vanadium compound (V compound) and having an adjusted temperature, as shown in Table 2A. When coating the surface treatment metal agent on the plating layer, in some cases the plating layer was subjected to a Co treatment.
[0074] The steel sheet having the plating layers on both sides was degreased using a degreaser (alkaline degreaser manufactured by Nippon Parkerizing Co., Ltd., product name: Fine Cleaner E6406) (20 g / L make-up bath, 60°C, 10-second spray, spray pressure 50 kPa), and then rinsed with water for 10 seconds using a spray.
[0075] The viscosity of the surface treatment metal agent in each example at 25°C was within the range of 0.5 mPa·s to 2.0 mPa·s.
[0076] In the table, in the "Silane coupling agent" category of organosilicon compounds, A1, A2, and B1 represent the following. A1: 3-aminopropyltrimethoxysilane A2: 3-aminopropyltriethoxysilane B1: 3-glycidoxypropyltrimethoxysilane
[0077] In addition, in the V compound, Z1 and Z2 are as follows. Z1: Vanadium oxysulfate VOSO 4 , Z2: Vanadium oxyacetylacetonate VO(OC(=CH 2 )CH 2 COCH 3 ) 2 .
[0078] The surface treatment metal agent was applied and naturally dried at a holding temperature of 25°C and at a holding humidity shown in Table 2C for the coating holding time shown in Table 2C. The steel sheet was then heated to the maximum sheet temperature shown in Table 2C, dried and baked. The start of the coating holding time for natural drying was immediately after the application of the surface treatment metal agent, and the end of the holding time was when heating for heat drying began.
[0079] The obtained coating film was evaluated for surface roughness, number density of the organosilicon compound, dynamic friction coefficient, corrosion resistance, and paint adhesion. The evaluation methods were as follows.
[0080] <Sa, Sz and Sq in a rectangular area with one side measuring 5 μm> On the surface of the coating, 20 areas were arbitrarily set as measurement areas of 5 μm square. Sa, Sz, and Sq were measured in each measurement area. A scanning probe microscope (AFM5500M manufactured by Hitachi High-Tech Science Corporation) was used as the measurement device, and the measurement mode was set to dynamic focus microscope mode. The probe used was SI-DF20, and the tip radius was set to 10 nm. The average values of the measurement results of each of the 20 measurement areas were taken as Sa, Sz, and Sq in a rectangular area of 5 μm on one side of the coating surface.
[0081] <Sa, Sz, and Sq in a rectangular area with one side measuring 1 μm> On the surface of the coating, 40 areas were set as measurement areas of 1 μm square. Of the 40 measurement areas, 20 measurement areas were set within the 20 5 μm rectangular measurement areas described above, and the remaining 20 were set arbitrarily from positions different from the 5 μm rectangular areas. Sa, Sz, and Sq were measured in each measurement area. The measurement device, measurement mode, probe, and tip radius were as described above. The average values of the measurement results of each of the 40 measurement areas were taken as Sa, Sz, and Sq in the rectangular area of 1 μm on one side of the coating surface.
[0082] <Number density of organosilicon compounds> The measurement areas set in the measurement method for Sa, Sz, and Sq in a rectangular area with one side of 1 μm were used to measure the number density of the organosilicon compound. In these multiple measurement areas, images were measured using the measurement mode of a dynamic focus microscope. The organosilicon compounds in the images were identified, and the number and size of the identified organosilicon compounds were measured. The average values were calculated from the measurement results in the multiple measurement areas, and these were used as the maximum diameter and number density.
[0083] An electron probe microanalyzer (EPMA) and a Fourier transform type micro infrared spectrophotometer (micro FT-IR) were used to identify organosilicon compounds in images taken with a dynamic focus microscope. The micro FT-IR measurements were performed in reflection measurement mode. Si was detected using the EPMA, and the periphery of the detected Si was measured using the micro FT-IR. When an infrared spectrum corresponding to the organic part of the organosilicon compound was obtained, the region where the infrared absorption spectrum was obtained was identified as an organosilicon compound. The average values were calculated from the results in multiple measurement regions, and these were used as the maximum diameter and number density.
[0084] <Kinematic friction coefficient> Using a friction tester manufactured by Shinto Scientific Co., Ltd., the dynamic friction coefficient of the coating surface was measured at a moving speed of 150 mm / min and a load of 1.0 N, using a SUS ball with a tip of 10 mmφ as the sliding contact. Measurements were also taken in a state where anti-rust oil was applied. The evaluation results were as follows:
[0085] 3: Dynamic friction coefficient is 0.2 to 0.5 2: Dynamic friction coefficient is 0.15 or more and less than 0.2 1: Dynamic friction coefficient is less than 0.15
[0086] <Corrosion resistance> The plate test pieces were subjected to a salt spray test in accordance with JIS Z 2371 for a specified period of time. The evaluation criteria for corrosion resistance are as follows. A rating of 3 or higher was considered a pass.
[0087] (Salt spray test after 72 hours) 4:5% or less 3: White rust more than 5% and less than 15% 2:White rust more than 15% and less than 30% 1: White rust over 30%
[0088] <Paint adhesion> The test panels were painted under the following conditions, and a paint film adhesion test was carried out. (Painting conditions) Painting conditions Paint: Amirac #1000 (registered trademark) (white paint) manufactured by Kansai Paint Co., Ltd. Painting method: Barcoat method Baking and drying conditions: 140℃, 20 minutes Coating thickness: 25μm The evaluation method is as follows.
[0089] (Primary adhesion) A test plate was cut with an NT cutter into 100 1mm squares, and a peeling test was performed using adhesive tape. The number of pieces of the coating that peeled off was used to evaluate the results. The evaluation criteria are as follows (a score of 3 or higher is practical and is considered a pass): The term "number of peeled pieces" used here refers to the number of pieces in which more than half of each grid was peeled off (the "number of peeled pieces" described below has the same meaning).
[0090] 4: Less than 1 peeled piece 3: Number of peeled pieces is 1 or more but less than 10 2: The number of peeled pieces is 10 or more and less than 50 1: 50 or more peeled pieces
[0091] (Secondary adhesion) The test plate was immersed in boiling water for 2 hours and left overnight, after which 100 1mm squares were cut into the plate using an NT cutter, and a peeling test was carried out using adhesive tape. The evaluation was based on the number of pieces of coating that peeled off. The evaluation criteria are as follows (a score of 3 or higher is practical and passes the test):
[0092] 4: Less than 1 peeled piece 3: Number of peeled pieces is 1 or more but less than 10 2: The number of peeled pieces is 10 or more and less than 50 1: 50 or more peeled pieces
[0093] In Table 2A, the blending ratio (A / B) of the silane coupling agent (A) and the silane coupling agent (B) is the solid mass ratio. The ratio (Y / W) of the phosphoric acid compound is the ratio of the solid mass of P derived from the phosphoric acid compound to the solid mass of Si derived from the organosilicon compound. The ratio (X / W) of the fluorine compound is the ratio of the solid mass of F derived from the fluorine compound to the solid mass of Si derived from the organosilicon compound. The ratio (Z / W) of the V compound is the ratio of the solid mass of V derived from the vanadium compound to the solid mass of Si derived from the organosilicon compound.
[0094] As shown in Tables 1 to 2C, in Examples 1 to 37, the dynamic friction coefficient was 0.2 to 0.5 in an unoiled state, and less than 0.15 in an oiled state. This is comparable to the dynamic friction coefficient of a conventional chromate coating, and no collapse occurs when multiple plated steel sheets are stacked flat. Furthermore, when the plated steel sheets are roll-formed, the same settings as those for the chromate coating can be used, and there is no need to readjust the settings of the processing.
[0095] Furthermore, Examples 1 to 37 were also excellent in corrosion resistance and coating adhesion.
[0096] On the other hand, in Comparative Examples 1 to 6, the dynamic friction coefficient was less than 0.2 in the unoiled state, and was also less than 0.2 in the oiled state. This is different from the dynamic friction coefficient of conventional chromate coatings, and the dynamic friction coefficient in the unoiled state was particularly low, causing the stack to collapse when multiple plated steel sheets were stacked flat. In addition, the paint adhesion was also insufficient.
[0097] [Table 1]
[0098] [Table 2A]
[0099] [Table 2B]
[0100] [Table 2C] [Explanation of symbols]
[0101] 1... surface-treated metal sheet, 11... steel sheet, 12... plating layer, 13... coating.
Claims
1. A steel plate, a zinc-containing plating layer formed on the steel sheet; and a chromate-free coating formed on the plating layer, The coating contains an organosilicon compound, a phosphoric acid compound, and a fluorine compound, When the surface roughness of a rectangular region of the surface of the coating having sides of 5 μm is expressed by an arithmetic mean height Sa, a maximum height Sz, and a root-mean-square roughness Sq, the arithmetic mean height Sa satisfies 0.10 to 10 nm, the maximum height Sz satisfies 1.0 to 1000 nm, and the root-mean-square roughness Sq satisfies 0.10 to 100 nm, A surface-treated metal sheet having a dynamic friction coefficient in the range of 0.2 to 0.
5.
2. The surface-treated metal sheet according to claim 1, characterized in that, when the surface roughness of a rectangular region of the surface of the coating, each of which has sides of 1 μm, is expressed as an arithmetic mean height Sa, a maximum height Sz, and a root-mean-square roughness Sq, the arithmetic mean height Sa satisfies 0.10 to 10 nm, the maximum height Sz satisfies 1.0 to 1000 nm, and the root-mean-square roughness Sq satisfies 0.10 to 100 nm.
3. 3. The surface-treated metal sheet according to claim 1, wherein the coating contains 1 to 100 granular organosilicon compounds each having a major axis of 10 nm to 300 nm within a rectangular region of 1 μm on a surface thereof.
4. The average chemical composition of the plating layer is, in mass%, Al: more than 4.0% to less than 25.0%; Mg: more than 1.0% to less than 12.5%; Sn: 0% to 20%, Bi: 0% to less than 5.0% In: 0% to less than 2.0% Ca: 0% to 3.0%, Y: 0% to 0.5%, La: 0% to less than 0.5%, Ce: 0% to less than 0.5% Si: 0% to less than 2.5%; Cr: 0% to less than 0.25% Ti: 0% to less than 0.25% Ni: 0% to less than 0.25% Co: 0% to less than 0.25% V: 0% to less than 0.25%, Nb: 0% to less than 0.25% Cu: 0% to less than 0.25% Mn: 0% to less than 0.25%; Fe: 0% to 5.0%, Sr: 0% to less than 0.5% Sb: 0% to less than 0.5% Pb: 0% to less than 0.5% B: Contains 0% to less than 0.5%; The surface-treated metal sheet according to claim 1 , wherein the balance is Zn and impurities.
Citation Information
Patent Citations
Information processor
JP1978035434A
Controls for tankless pumps
JP1978036002A
Surface treated steel sheet having excellent white rust resistance, and production method therefor
JP2003105554A
Chromate-free surface-treated metal material excellent in corrosion resistance, heat resistance, fingerprint resistance, conductivity, coatability and black-dreg resistance at processing
JP2007051365A
Surface treatment agent and steel sheet
JP2011225942A